Evaluating effectiveness of optical burst switching networks by analytical models using queuing principle M/M/w/w and simulation on OMNeT++. - Bình, Lê Hữu; Bình, Lê Nguyên; Võ, Hoàng Văn (Journal of Computer Science and Cybernetics, 2013)
Optical Burst Switching (OBS) has become one of the most important techniques for next generations of ultra-high speed optical internetworking. Performance evaluation of OBS networking models is thus very critical in the evaluation of the effectiveness of different routing and switching algorithms. This paper presents both computer simulation and analytical models for evaluating the effectiveness of OBS networking, especially the burst blocking probability. We develop a simulation model for OBS networking, namely OBSWDM-Simu based on OMNeT++ platform. The model is capable of simulating control protocols of OBS networks and simultaneously incorporating the impacts of physical layer effects on the blocking probability. We also present the analytical models for OBS networking based on the queuing theory in order to compare with the results of OBSWDM-Simu model.